1998
DOI: 10.1029/98jd02280
|View full text |Cite
|
Sign up to set email alerts
|

Airborne studies of aerosol emissions from savanna fires in southern Africa: 2. Aerosol chemical composition

Abstract: Abstract. We investigated smoke emissions from fires in savanna, forest, and agricultural ecosystems by airborne sampling of plumes close to prescribed burns and incidental fires in southern Africa. Aerosol samples were collected on glass fiber filters and on stacked filter units, consisting of a Nuclepore prefilter for particles larger than -• 1-2 gm and a Teflon second filter stage for the submicron fraction. The samples were analyzed for soluble ionic components, organic carbon, and black carbon. Onboard th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(176 citation statements)
references
References 46 publications
9
163
2
2
Order By: Relevance
“…6) suggests that in our samples the resuspension of soil dust was much less important to 210 Pb emissions than biomass burning. Biomass burning aerosols also contain sulfate, organic and elemental carbon, and other organic species (e.g., Gaudichet et al, 1995;Andreae et al, 1998). This is in agreement with our samples.…”
Section: Saharan Dust and Biomass Burningsupporting
confidence: 82%
“…6) suggests that in our samples the resuspension of soil dust was much less important to 210 Pb emissions than biomass burning. Biomass burning aerosols also contain sulfate, organic and elemental carbon, and other organic species (e.g., Gaudichet et al, 1995;Andreae et al, 1998). This is in agreement with our samples.…”
Section: Saharan Dust and Biomass Burningsupporting
confidence: 82%
“…However such events are not frequent and none one of the events identified in Guan et al (2010) coincides with the eruptions studied here. Also no clearly elevated concentrations of K in excess of the ash concentration are seen in the samples, which would be expected from fires (Andreae et al, 1998). One alternative explanation is the carbon content of the air that is entrained into the volcanic jet and lifted with the volcanic effluents.…”
Section: Carbonaceous Aerosol In Volcanic Cloudsmentioning
confidence: 87%
“…However, the SEM/EDX analyses showed that there was an unusually high proportion of K in S-rich particles during the episode, especially at the beginning of the episode. This is a clear indication of emissions from biomass burning, because K in the fine size fraction is well known as a good tracer of biomassburning aerosols (Andreae, 1983;Andreae et al, 1998). The trajectories and fire area map (see Figs.…”
Section: Article In Pressmentioning
confidence: 99%